2012
DOI: 10.1590/s1415-790x2012000200003
|View full text |Cite
|
Sign up to set email alerts
|

Added sugars: consumption and associated factors among adults and the elderly. São Paulo, Brazil

Abstract: Objective: To investigate added sugar intake, main dietary sources and factors associated with excessive intake of added sugar. Methods: A population-based household survey was carried out in São Paulo, the largest city in Brazil. Cluster sampling was performed and the study sample comprised 689 adults and 622 elderly individuals. Dietary intake was estimated based on a 24-hour food recall. Usual nutrient intake was estimated by correcting for the within-person variance of intake using the Iowa State Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 17 publications
(21 reference statements)
6
9
0
10
Order By: Relevance
“…Bueno et al [35], in a study with 689 adults and 622 elderly individuals from São Paulo, Brazil, also found that the soft drinks were a major source of added sugars among adults, and table sugar was the major source among the elderly. Soft drinks and table sugar (refined sugar, brown sugar, and molasses) represented more than 50% of added sugars in all sex and age groups studied.…”
Section: Discussionmentioning
confidence: 94%
“…Bueno et al [35], in a study with 689 adults and 622 elderly individuals from São Paulo, Brazil, also found that the soft drinks were a major source of added sugars among adults, and table sugar was the major source among the elderly. Soft drinks and table sugar (refined sugar, brown sugar, and molasses) represented more than 50% of added sugars in all sex and age groups studied.…”
Section: Discussionmentioning
confidence: 94%
“…Strong evidence indicates that self-reported energy intakes underestimate energy needs. This evidence comes from studies in which energy needs were derived from weight maintenance data 29,30 , doubly labeled water assessments 31 , and total energy expenditure prediction equations 32,33 . However, none of these studies have examined the measurement error according to food groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bueno et al 45 , em um inquérito populacional domiciliar, realizado com adultos e idosos da cidade de São Paulo, mostraram que 27,1% dos idosos apresentaram uma ingestão de açúcar adicionado maior que 10% da ingestão de energia. Contudo, esta frequência foi significativamente menor que nos adultos (38,1%).…”
Section: Artigo De Revisãounclassified
“…Porém, a principal fonte destes açúcares foi o refrigerante entre os adultos e o açúcar de mesa entre os idosos. A média do consumo dos açúcares adicionados foi maior entre as mulheres 45 .…”
Section: Artigo De Revisãounclassified